157 Survey on use of Caffeine in Apnoea of Prematurity in Neonatal Units Across England. (October 2012) - Abraham, D; Rajagopal, P; Curtis, E; Manzoor, A; Ahmed, M
Abstract : Background: Apnoea of prematurity (AOP) is a significant clinical problem in premature infants and is almost universal in infants < 1000 g at birth. Caffeine has emerged as the methylxanthine of choice to treat AOP. Although it is commonly used, there is no unified consensus or guideline on its use in NNUs in England. Aim: To study the current practice of caffeine use in AOP at NNUs in England. Methods: A telephonic survey of level 3 and level 2 units in England was conducted, using a standardised questionnaire, over November and December, 2011. Results: Out of 52 units surveyed, 48% were level 3 units. All units used caffeine for treatment of AOP (base 60% and citrate 40% of units). 92% of units have written guidelines on caffeine use. Caffeine was started by 47% of units based on gestational age, regardless of symptoms.[IS3] All units used a loading dose, which varied between 5 and 25mg/kg (median of 10mg/kg) for caffeine base and 15 to 20mg/kg (median of 20mg/kg) for citrate. The maintenance dose varied between 2.5–6mg/kg/day (median of 5mg/kg/day) for base and 5–12mg/kg/day (median of 5mg/kg/day) for citrate. Caffeine levels were routinely performed by 7% of units. Caffeine was discontinued between 30 to 36 weeks gestation. Discussion: Our survey depicts that practice of caffeine use varies significantly across NNUs in England. The results from this survey could be used as a footing for further data collection, for formulation of a uniform guideline maximising the utilisation of this extensively studied drug.